Proteomic profiling of the coagulation of milk proteins induced by glucono-delta-lactone. (January 2016) - Chen, Ying-Ching; Chen, Chun-Chi; Chen, Shui-Tein; Hsieh, Jung-Feng
Abstract: This study investigated the glucono-delta-lactone (GDL)-induced coagulation of milk proteins at 30 °C. The addition of 0.5 M GDL caused milk proteins to coagulate following a 1 h incubation period. Approximately 90.7% of milk proteins were coagulated into the milk pellet fraction (MPF), and the protein concentration of the milk supernatant fraction (MSF) decreased from 29.2 ± 1.1 mg mL −1 (control) to 2.7 ± 1.1 mg mL −1 . The SDS-PAGE analysis demonstrated that the protein bands corresponding to α S -casein, β -casein and κ -casein in the MSF decreased to 0.2 ± 0.1, 0.5 ± 0.2 and 0.5 ± 0.3% of their original levels, respectively. However, only 29.5% of the β -lactoglobulin was coagulated into the MPF following the treatment with 0.5 M GDL. Two-dimensional electrophoresis analysis indicated that isomers of α S1 -casein, α S2 -casein, β -casein and κ -casein, as well as a fraction of β -lactoglobulin and α -lactalbumin, were coagulated from the MSF into the MPF following incubation with 0.5 M GDL. Graphical abstract: The α S1 -casein, α S2 -casein, β -casein, and κ -casein as well as a fraction of β -lactoglobulin and α -lactalbumin were coagulated by 0.5 M GDL. Highlights: We analyzed the coagulation of milk proteins using a proteomics approach. The addition of 0.5 M GDL to milk induces the destabilization of casein micelles. The α S1 -CN, α S2 -CN, β -CN, κ -CN, β -LG and α -LA were coagulated by 0.5 M GDL. The proteomics approach is a useful tool for the analysis of milk proteins.